Súmulas e precedentes judiciais trabalhistas: distinções e análises necessárias - Parise, Lara Careta (2022)
The Civil Procedure Code of 2015 introduced decisions and institutes that moves towards the consolidation of judicial precedents in the Brazilian legal system, by establishing, in § 1, items V and VI of article 489 and articles 926 and 927, the system applied to judicial precedents. In its article 927, it provided a list of hypotheses that will constitute precedents, giving them binding force. Considering the subsidiary and supplementary application of the Civil Procedure Code to the procedural labor law, in case of omission and compatibility (art. 769 CLT and art. 15 CPC), it was edited a Normative Instruction n. 39/2016, which in items IX and XXIII of article 3, article 8 and caput and items of article 15 allows and suggests the application of the institutes of the assumption of competence incident, the incident of resolution of repetitive demands and the constitutional claim, as well as in items I and II of article 15, that establishes the hypotheses that will be treated as precedents within the scope of the Labor Process. In the Labor Court, the “súmula” have a fundamental role of jurisprudential standardization and integrate the labor procedural system alongside the precedents. However, the particularities of the Brazilian system cause doubts that demand a detailed study about judicial precedents and “súmulas”, so that the detailed study of the distinctions of the institutes allows the understanding and correct application, allowing an evolution and consolidation of the system, in a way that to achieve a greater degree of satisfaction and reliability and further away from doubts. In this context, the present dissertation aims to delineate the fundamental differences between “súmulas” and judicial precedents, focusing on the reverberations in the scope of the work process, passing through the study of compatibility of the institutes in the face of the Brazilian model of formally binding judicial precedents. To this goal, the study will adopt the critical-methodological line, under the legal-dogmatic aspect and, as sources of production of legal knowledge, legislation, doctrine and works of Law will be used, adopting as a theoretical framework the theory developed by Hermes Zaneti Jr.